2020
DOI: 10.3390/molecules25061343
|View full text |Cite
|
Sign up to set email alerts
|

Improving Dissolution and Cytotoxicity by Forming Multidrug Crystals

Abstract: Both rosiglitazone and metformin have effects on blood glucose regulation and the proliferation of liver cancer cells. Combination therapy with these two drugs is common and effective for the treatment of diabetes in the clinic, however, the application of these two drugs is influenced by the poor dissolution of rosiglitazone and the gastrointestinal side-effect of metformin resulting from a high solubility. The formation of a multidrug crystal form (Rsg-Met) by a solvent evaporation method can solve the solub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…It can be seen that CEP was a bisbenzylisoquinoline alkaloid with weak base, so that it had high solubility under acidic condition (45). Additionally, several studies have shown that the absorption of weak base in the gastrointestinal tract occurs predominantly in the intestine (pH=5~7) (46,47). Whence, it is necessary to enhance the poor dissolution of CEP in the weak base medium to improve oral bioavailability.…”
Section: In Vitro Release Experimentsmentioning
confidence: 99%
“…It can be seen that CEP was a bisbenzylisoquinoline alkaloid with weak base, so that it had high solubility under acidic condition (45). Additionally, several studies have shown that the absorption of weak base in the gastrointestinal tract occurs predominantly in the intestine (pH=5~7) (46,47). Whence, it is necessary to enhance the poor dissolution of CEP in the weak base medium to improve oral bioavailability.…”
Section: In Vitro Release Experimentsmentioning
confidence: 99%
“…After excluding entries corresponding to the MTF base molecule and its inorganic salts (4) as well as MTF metal complexes (29), the remaining dataset contained 26 molecular salts (44%). From the remaining molecular salts, 13 entries corresponded to MTF–drug salts, mainly antidiabetic drugs [ 34 , 35 , 36 , 37 , 38 ]. Only three salt structures containing MTF and an NSAID as counterion have been reported: MTF–diclofenac [ 39 ], MTF–salicylate [ 40 ], and MTF–aspirin [ 41 ] salts.…”
Section: Resultsmentioning
confidence: 99%
“…Based on clinical studies, nausea, vomiting, diarrhea, and other gastrointestinal side effects occur in 20-30% of patients taking metformin hydrochloride [30]. Considering the above problems, researchers have carried out multicomponent co-crystallization studies on MET via salification strategy [6,11,[31][32][33][34][35][36][37][38][39][40][41][42]. However, these literature reports mainly focused on the optimization of MET physicochemical properties, and no pharmacological evaluation has been conducted on the hypoglycemic effect of multicomponent salts in vivo.…”
Section: Introductionmentioning
confidence: 99%